Визначення проблем розвитку готельно-ресторанного бізнесу на основі фінансово-статистичної звітності - Якименко-Терещенко, Наталія Василівна; Побережна, Наталія Миколаївна; Хо, Жань (ТОВ "ДКС Центр", 2021)
Реалії, в яких опинились суб’єкти готельно-ресторанного бізнесу, вимагають від них вміння правильно ідентифікувати та оцінювати поточний стан, тенденції подальшого розвитку, а також розробляти ефективні стратегічні управлінські рішення, реалізовувати тактичні дії щодо адаптації до мінливих та складних умов зовнішнього середовища. Стаття присвячена дослідженню стану, результатів функціонування, а також визначенню різнорівневих управлінських заходів щодо подальшого розвитку суб’єктів готельно-ресторанного бізнесу. Увага була приділена дослідженню фінансової результативності їх діяльності в період пандемії, змінам їх кількісного складу, а також зв’язку виявленої негативної динаміки зі змінами показників споживання та витрат домашніх господарств в Україні. Виокремлено проблеми суб’єктів готельно-ресторанного бізнесу, а також акцентовано увагу на ключовому значенні підтримки та стимулювання розвитку даної сфери діяльності на макрорівні.

The realities in which the subjects of the hotel and restaurant business find themselves require from them the ability to correctly identify and assess the current state, trends for further development, as well as develop effective strategic management decisions, implement tactical actions to adapt to changing and difficult environmental conditions. The article is devoted to the study of the state, the results of functioning, as well as the definition of multi-level management measures for the further development of the subjects of the hotel and restaurant business. A study of the financial performance of their activities during a pandemic, changes in their quantitative composition, as well as the relationship of the identified negative dynamics with changes in consumption and household expenditures in Ukraine was carried out. Analysis of statistical data grouped by financial and statistical reporting of enterprises of the hotel and restaurant and tourism business indicates a steady trend of reducing infrastructure tourism resources and the presence of a number of problems in the field of hotel and restaurant business, was strengthened by quarantine restrictions. The problems of the subjects of the hotel and restaurant business are highlighted, and focused on the key importance of supporting and stimulating the development of this area of activity at the macro level. At the macro level, it is necessary to implement strategic measures: develop a market ecosystem and public-private partnership, create a mechanism and conditions for attracting investment, provide sustainable financial support for hospitality, implement a mechanism for state support of innovative projects in hospitality. At the micro level, it is necessary to: diversify the provision of services by enterprises in terms of assortment and price; improve the quality of services, bring them up to European standards; improve the efficiency of organizing business processes in the hotel and restaurant business; use marketing concepts as a central management tool for hospitality establishments; сonstantly develop staff; integrate the Internet into the formation of consumer preferences and behavior; introduce innovations and innovative technologies that contribute to attracting new customers, maximizing sales, gaining guest confidence and creating a positive image of the enterprise.
Identify the development problems of the hotel and restaurant business through financial and statistical reporting
Keywords: готельно-ресторанний бізнес; розвиток; управління; звітність; туризм; hotel and restaurant business; development; management; reporting; tourism